Municipal solid waste in Mar del Plata, Argentina: environmental problem or inputs for industry? - Gonzalez Insua, Mariana (2015)
Starting from the Conference of the United Nations about Environment and Development, the basis for an integral handling of the Solid Residues as part of a Sustainable Development are established. In this context, Argentina develops the National Strategy for Management of Urban Solid Waste (ENGIRSU) in the year 2005. One of the strategies for the study of residues as materials potential to evaluation is the analysis of the Chain of Value. The present work has as objectives to contribute to the knowledge of the Integral Management of Urban Solid Residues in the city of Mar de Plata, and to analyze the revaluation of these in the Formal Circuit (CF) of recuperation under the perspective of the Chain of Value, visualizing its principal actors, their power, and their control inside the chain. In order to achieve the objective, we present a historical-environmental journey through the problem of waste in Argentina until the development of ENGIRSU; pointing out the analysis of the strategic implementation in the city of Mar del Plata focusing on the waste separation stage, specifically at the Separation and Classification Plant operated by CURA Cooperative. As a result, the analysis shows a low productivity in the plant as component of the GIRSU and a weak role as link inside the Chain of Value of Urban Solid Waste.